2018
DOI: 10.1186/s13006-018-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Prelacteal feeding and associated factors among newborns in rural Sidama, south Ethiopia: a community based cross-sectional survey

Abstract: BackgroundThe practice of giving prelacteal feeds deprive a newborn of valuable nutrients and expose the newborn to risks of infection. Despite its negative health outcomes, prelacteal feeding prevails in Ethiopia. Therefore, the current study was undertaken to assess the prevalence of prelacteal feeding practices and its associated factors in a rural community in south Ethiopia.MethodsWe conducted a community based cross-sectional study of 597 mothers of children aged less than six months. Mothers were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 13 publications
9
56
2
Order By: Relevance
“…For example, a report from Eastern Uganda by Engebretsen et.al [26], found that 57% of mothers had given pre-lacteal feeds. Nevertheless, a lower prevalence of PLF was reported from the Kilimanjaro region in northern Tanzania (1%) [27], and from northwest (26.8%) [28] and south Ethiopia(25.5%) [7]. Whereas some low income countries have extension community health workers who move among the villages promoting recommended maternal and newborn care practices [7], such programs are non-existent in South Sudan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a report from Eastern Uganda by Engebretsen et.al [26], found that 57% of mothers had given pre-lacteal feeds. Nevertheless, a lower prevalence of PLF was reported from the Kilimanjaro region in northern Tanzania (1%) [27], and from northwest (26.8%) [28] and south Ethiopia(25.5%) [7]. Whereas some low income countries have extension community health workers who move among the villages promoting recommended maternal and newborn care practices [7], such programs are non-existent in South Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a lower prevalence of PLF was reported from the Kilimanjaro region in northern Tanzania (1%) [27], and from northwest (26.8%) [28] and south Ethiopia(25.5%) [7]. Whereas some low income countries have extension community health workers who move among the villages promoting recommended maternal and newborn care practices [7], such programs are non-existent in South Sudan. The lack of organized programs that specifically focus on promotion of breastfeeding might explain the high prevalence of PLF in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This harmful prelacteal feeding practice has been widely documented in almost all administrative regions of Ethiopia. The magnitude of prelacteal feeding practices reported in the whole country ranges 15 to 45.5% [7,8,[10][11][12][13][14]. The predictors of prelacteal feeding practices were found to be: socio-demographic characteristics, Ante-Natal Care, place of delivery, Post-Natal Services and counseling services received on infant feeding and early initiation of breastfeeding [7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies show that infant feeding practices are inadequate in marginalized communities (Exavery et al 2015;Horii et al 2017;Khan et al 2017). These communities also initiate late breastfeeding (Alebel et al 2017), and fed prelacteals (Chea and Asefa 2018;Jama et al 2017;Thepha et al 2018). In addition to these practices, similarly in other studies, mothers, showed that they neglected full exclusive breastfeeding and followed partial exclusive breastfeeding (Mohamed et al 2018;Quinlivan et al 2015).…”
Section: Discussionmentioning
confidence: 99%